Klasifikasi Sentimen SVM Dengan Dataset yang Kecil Pada Kasus Kaesang Sebagai Ketua Umum PSI - El Saputra, Yoga; Agustian, Surya; Yusra, Yusra; Ramadhani, Siti (STMIK Budi Darma, 2024)
Social media has become the main platform for the public to express views and opinions on various events, including the appointment of Kaesang Pangarep as General Chair of the Indonesian Solidarity Party (PSI). This research aims to classify public sentiment towards the appointment using the Support Vector Machine (SVM) method with the Term Frequency-Inverse Document Frequency (TF-IDF) approach. Data was collected from Twitter using the keyword